The Shooting Method for the Numerical Solution of the Poisson Equation: A Control Viewpoint - Schaerer, C.E.; Kaszkurewicz, E.; Mangiavacchi, N. (Trends in Computational and Applied Mathematics, 2003)
A discrete-space state representation is used to provide a feedback control-theoretical formulation for the iterative shooting method. This method historically defined for boundary value problem in ordinary differencial equations, specifically it is focused on the numerical solution of the Poisson equation, which leads to a new a more efficient method for the solution of this type of equations.